Relations between different coping strategies for social stress, tumor development and neuroendocrine and immune activity in male mice - Azpiroz, A.; De Miguel, Z.; Fano, E.; Vegas, O. (Brain, behavior, and immunity, 2008)
This study analyzes the effects of acute social stress and different coping strategies employed in response to it on the development of B16F10 melanoma pulmonary metastases, the activation of the HPA axis and the NKG2D receptor expression. To this end, male OF1 mice were subjected to 24 h of social stress using the sensorial contact model. This model includes three 5-min sessions of direct social interaction with resident cagemates selected for consistent levels of aggression. Subjects’ behavior was videotaped and assessed. Six days after the first social interaction (1st social stress), the animals were inoculated with tumor cells or vehicle, and six days later, both tumor-bearing and non tumor-bearing mice were subjected to a second 24 h sensorial contact social stress session (2nd social stress). One hour after the 2nd social interaction, corticosterone levels and NKG2D receptor expression were determined. Lung metastatic foci numbers were determined 21 days after inoculation (15 days post-stress). Social stress increased the number of pulmonary metastases and the serum corticosterone level. A combination of cluster and discriminant analyses established the existence of two types of coping strategies: (1) a passive–reactive strategy characterized by subjects dedicating a greater percentage of time to submission, flee and avoidance behaviors; and (2) an active–proactive strategy, characterized by subjects dedicating a greater percentage of time to attack and non social exploration behaviors. Subjects belonging to the passive–reactive group were found to have a higher number of tumor foci, a higher level of corticosterone and a lower NKG2D receptor expression than subjects in the active–proactive group. These data indicate the relationship between different coping strategies for social stress and tumor development.